Pola Komunikasi Tata Niaga Tembakau (Studi Kasus Grader Tembakau dan Petani Tembakau di Kecamatan Parakan) - Krisdian Arifianto; Astri Wulandari (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2023)
In the process of tobacco trading, the factory has a representative who is trusted to buy and accommodate the tobacco harvest. Factory representatives are known as graders whose job is to determine the price of tobacco based on the tobacco yield figures offered by farmers to factories. This study aims to look at communication patterns in the tobacco trading process system involving graders where this has weaknesses, namely allegations of malfeasance in graders that are trusted by factories as a sale and purchase agreement that is not stated in writing between farmers and graders so that graders can freely drop the prices. This research uses a qualitative descriptive method with a case study approach in Parakan District, Central Java. The results show that the pattern of primary communication between graders and farmers has weaknesses, namely being constrained by the distance and the activity of the graders. Furthermore, for secondary communication patterns, there are media that link messages between graders and farmers, linear communication patterns that are one-way and tend to be detrimental and circular communication patterns that are able to minimize crop failure and create a good communication climate.